Wireless sensor and mobile ad-hoc networks : vehicular and space applications - Benhaddou,Driss (Springer, 2015)
This book describes the practical perspectives in using wireless sensor networks (WSN) to develop real world applications that can be used for space exploration. These applications include sensor interfaces, remote wireless vehicles, space crew health monitoring and instrumentation. The material discusses how applications of WSN originally developed for space travel and exploration are being applied and used in multiple real world applications, allowing for the development of smart systems that have characteristics such as self-healing, self-diagnosis, and emergency healthcare notification. This book also: · Discusses how multidisciplinary fields can be implemented in a single application · Reviews exhaustively the state-of-the-art research in WSN for space and vehicular applications · Covers smart systems that have self-healing, self-diagnosis, and emergency healthcare notification-- Back Cover.